Analisis Waste (Pemborosan) pada Instalasi Farmasi Rawat Jalan Menggunakan Pendekatan Lean Management di RS PKU Muhammadiyah Bantul - Triyani Triyani; Firman Syarifuddin (International Journal of Healthcare Research, 2020)
Background: Pharmacy installation is the last unit that determines patient satisfaction in hospital services, so that the good or bad service provided will affect the related service units. Problems that often occur include slow pharmacy services, complicated procedures and difficulties for patients. Lean is an effort to eliminate waste and increase the value added of products both goods and services that take place continuously with the aim of providing value to customers. Outpatient Pharmacy Services at PKU Muhammadiyah Hospital in Bantul have not applied Lean. The purpose of this study is to find out the existence of waste in Outpatient Pharmacy Installation of PKU Muhammadiyah Hospital in Bantul Method: This type of research is a case study with a qualitative approach. Location of research in PKU Muhammadiyah Hospital, Bantul. The subject of this study was the pharmacy manager and head of the outpatient pharmaceutical unit. The instruments in this study used observation and interview guides. Data analysis uses triangulation methods and sources. Results: Based on Value Stream Mapping (VSM) mapping, non-racic Non Value Added (NVA) values were obtained 68.21% and 57.59%, which meant that the hospital had not been said to be lean. The critical waste that occurs is waste waiting and overprocessing. The cause of waste waitting is that the SIM sometimes has errors, many officers have double jobs, while overprocessing is caused by many repeated activities, such as repeated prescription studies and etiquette writing twice. Conclusion: This NVA value is more than 30% indicating that the service has not been effective and efficient and there is waste. Waste that often occurs in outpatient pharmaceutical installations in PKU Muhammadiyah Bantul Hospital, namely waiting, is good for non-racial and cosmetic prescription services while over-processing occurs in non-racial prescription services.